(untitled) (Journal of Pakistan Orthopaedic Association, 2020)
Objective: To determine the functional and radiological outcome of fracture distal femur treated with retrograde interlocking nail. Methods: This was a descriptive study conducted at Department of Orthopaedics surgery Jinnah Post Graduate Medical Centre(JPMC) from 15th February 2016 to 10th January 2019.All patients fulfilling the inclusion criteria were treated with retrograde nailing. Post operative functional outcome was evaluated with Schatzker and Lambert criteria as graded as excellent, good and poor. Radiologically union was assessed with x rays. Results: There were 97 patients with mean age of 35.20±10.66(range 20 to 50 years) of age. Male patients were 74(76.2%) and female 23(23.7%). Majority(70.1%,n=68) of fractures were due to motor vehicle accidents. Right side fracture was present in 60(61.9%) patients and left in 37(38.1%). Excellent outcome was noted in 72(74.2%) patients and good in 25(25.7%).No non union was documented. Conclusion: Excellent and good functional and radiological outcome was achieved in distal femur patients treated with retrograde interlocking nailing. We recommend retrograde interlocking nail as an implant of first choice for selected distal femur fractures.